Phenotypic Alterations Involved in CD8+ Treg Impairment in Systemic Sclerosis - Negrini, Simone; Fenoglio, Daniela; Parodi, Alessia; Kalli, Francesca; Battaglia, Florinda; Nasi, Giorgia; Curto, Monica; Tardito, Samuele; Ferrera, Francesca; Filaci, Gilberto (Frontiers in Immunology, 2017)
Systemic sclerosis (SSc) is a connective tissue disease characterized by tissue fibrosis, vasculopathy, and autoimmunity. Although the exact pathogenetic mechanisms behind SSc remain to be fully elucidated, a great deal of evidence suggests the existence of an unbalanced ratio between the effector and regulatory arms of the immune system. With regard to the T regulatory (Treg) compartment, we observed that CD8+ Treg subsets display functional defects in SSc-affected patients. Since CD127 down-modulation and CD39 upregulation have been observed on Treg subsets, the phenotypic expression of these molecules was analyzed on the CD8+CD28− Treg precursors and on CD8+ Treg cells generated in vitro through interleukin-10 commitment. Immunophenotypic data from SSc patients were compared to those obtained from healthy subjects. The analyses performed on ex vivo-isolated CD8+CD28− Treg precursors did not show any significant differences in CD39 or CD127 expression as compared to values obtained from healthy donors. On the contrary, in vitro-generated CD8+ Tregs obtained from SSc patients displayed reduced expression of the CD39 molecule as compared to controls. Moreover, the percentage of CD127+ cells was significantly higher in in vitro-generated CD8+ Tregs from SSc patients compared to CD8+ Tregs obtained from healthy donors. Taken together, these findings may indicate an impairment of maturation processes affecting CD8+ Treg cells in SSc patients. This impairment of maturation involves phenotypic alterations that are mainly characterized by a deficient CD39 upregulation and a lack of down-modulation of the CD127 molecule.